2014
DOI: 10.1038/nmat3993
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable liquid-crystal blue-phase gels

Abstract: Liquid-crystalline polymers are materials of considerable scientific interest and technological value. An important subset of these materials exhibit rubber-like elasticity, combining the optical properties of liquid crystals with the mechanical properties of rubber. Moreover, they exhibit behaviour not seen in either type of material independently, and many of their properties depend crucially on the particular mesophase employed. Such stretchable liquid-crystalline polymers have previously been demonstrated … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
86
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 30 publications
1
86
1
1
Order By: Relevance
“…In the bulk, however, BPs are only found in a narrow range of temperature, between the cholesteric and the isotropic phases (1-6, 10-18), thereby placing limits on their practical utility. Recent efforts have therefore focused on increasing their stability over wider ranges of temperature and chirality, for example through addition of nanoparticles (19, 20, 21-23), polymers (24-26), or by manipulating their flexoelectricity (14).Confined chiral liquid crystals are of interest for applications in optical devices (27)(28)(29)(30)(31). Simulations of chiral LCs in channels have shown that their defect structure can be manipulated through confinement, thereby raising intriguing prospects for technology (32)(33)(34)(35).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the bulk, however, BPs are only found in a narrow range of temperature, between the cholesteric and the isotropic phases (1-6, 10-18), thereby placing limits on their practical utility. Recent efforts have therefore focused on increasing their stability over wider ranges of temperature and chirality, for example through addition of nanoparticles (19, 20, 21-23), polymers (24-26), or by manipulating their flexoelectricity (14).Confined chiral liquid crystals are of interest for applications in optical devices (27)(28)(29)(30)(31). Simulations of chiral LCs in channels have shown that their defect structure can be manipulated through confinement, thereby raising intriguing prospects for technology (32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Confined chiral liquid crystals are of interest for applications in optical devices (27)(28)(29)(30)(31). Simulations of chiral LCs in channels have shown that their defect structure can be manipulated through confinement, thereby raising intriguing prospects for technology (32)(33)(34)(35).…”
mentioning
confidence: 99%
“…Recently, there have been significant advances in the technology of blue phases where polymer-stabilised formulations allow BPs to the used in a practically useful temperature range [8,19]. This holds out the promise of useful application in, e.g., photonics [5,6]. More recently, there has also been interest in nanoparticle stabilisation of BPs [18,38].…”
mentioning
confidence: 99%
“…245 The formation of LC gels has also been applied to the preservation of exotic LC phases such as blue phases that have intriguing photonic functions. [246][247][248][249] Remarkably, LC chemical gels also show shape variations in response to temperature and external fields. [250][251][252][253][254][255] Thermal actuation in LC chemical gels is often accompanied by volume variations.…”
Section: Functional Lc Polymers and Networkmentioning
confidence: 99%